Anti-hyperlipidemic potential of a combination of Zingiber officinale Roscoe, Allium sativum L., Citrus lemon (L.) Osbeck, Honey and Malus domestica Borkh. Cider Vinegar - Perumal, Kokila Vani (2022)
Intervention of herbal combination is widely used to decrease the risk of metabolic disorders such as cardiovascular diseases, hyperlipidemia, diabetes, and obesity. Hyperlipidemia is known as an abnormal lipid metabolism presents in the bloodstream which associated with co-morbidities and mortalities that grossly rising worldwide. The study aims to investigate the anti-hyperlipidemia activities of a combination of ZACAH mixture (Zingiber officinale Roscoe (ginger), Allium sativum L. (garlic), Citrus lemon (L.) Osbeck, Honey, and Malus domestica Borkh. Cider Vinegar in hyperlipidemic rats. High-performance liquid chromatography (HPLC) was performed to identify the phytochemical component that presents in the ZACAH mixture. 36 Sprague dawley (SD) rats were divided into 6 groups. ZACAH mixture (1ml/kg, 3 ml/kg, 5 ml/kg) was administered along with a high cholesterol diet (HCD) via oral gavage, daily for 18 weeks. Simvastatin 10 mg/kg was used as a standard drug. At end of week 18, the rats were sacrificed and blood and organs were collected for further experiments. The blood collection was performed for lipid profile (TC, TG, LDL), blood toxicity (Creatinine, AST, ALT), and enzymatic activity (HMG-CoA reductase, LCAT, ACAT2). Besides, liver, kidney and adipose tissue were performed for histological examination by using hematoxylin & eosin (H&E) stain. ZACAH mixture had ORAC value 2000 μmol TE/100 mL, TPC (7537 ± 54.5mg/100g GAE), 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity (27.34 ± 2.71%) , Elastase inhibitory assay (29.29 ± 1.65%) and Lipoxygenase inhibitory assay (98.58 ± 1.42%). The phytochemical component found in the ZACAH mixture is hesperidin. Bodyweight, total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL) reduced and an increase in high density lipoprotein (HDL) was observed in ZACAH mixture treated groups compared to the positive control (PC). ZACAH mixture treated groups reduced HMG-CoA reductase and ACAT2 activity led to a reduction of TC, TG, LDL and an increase in HDL. Histological examinations revealed that lipid accumulation was reduced in the liver tissue and the size of adipocytes was suppressed in the ZACAH mixture treated group as compared to the PC group. The findings demonstrate that the ZACAH mixture at 5ml/kg BW significantly (p<0.05) has a strong hyperlipidemia activity that can be an alternative approach to combat hyperlipidemia treatment.